Correlations study and clustering from SPI experiences in small settings. Issue 1 (12th September 2018) - Larrucea, Xabier; Santamaría, Izaskun
Abstract: Software Process Improvement (SPI) initiatives have been applied in a wide set of organisations including very small entities (VSE). In fact, this kind of organisations is facing several hurdles when overarching a SPI initiative. In this context, the ISO/IEC 29110 has been used as a lightweight reference model for steering VSEs in their SPI initiatives. The inherent uncertainty behind the SPI curtains blocks the organisations in their investments. Due to these reasons, we need to identify relationships and similarities in order to predict whether a SPI will succeed or not. We propose the use of Self‐Organising Maps for identifying patterns from these SPI studies. The aim of this paper is to identify correlations among SPI studies and to discover patterns from them.